Penganggaran Modal Multinasional dan Tantangan Risiko Global: Studi Kasus Pada PT Garuda Indonesia (Persero) TBK - Diah Ayu Nurmavita; Sinta Amelia; Muhammad Saddam; Perwito Perwito (Indonesia Economic Journal, 2026)
Multinational capital budgeting is a long-term investment decision-making process undertaken by multinational corporations, considering various cross-border factors. Unlike domestic capital budgeting, multinational capital budgeting faces additional complexities such as currency exchange rate fluctuations, differences in tax systems, political risk, global economic risk, and regulatory differences in host countries. This study aims to analyze the concept and practice of multinational capital budgeting and examine the risks and managerial implications that arise in its implementation. The research method used is a descriptive qualitative approach through a literature review of national and international journals, international finance textbooks, and the company's financial reports and official publications. A case study of PT Garuda Indonesia (Persero) Tbk is used to provide an empirical overview of the challenges of multinational capital budgeting, particularly those related to international funding and exchange rate risk. The study results indicate that cross-border investment decisions that are not balanced with adequate risk analysis can create significant financial pressures and threaten the company's sustainability. Therefore, multinational capital budgeting needs to be conducted comprehensively, considering aspects of profitability, risk, and long-term financial resilience.